Defects in high‑pressure die casting and measures to prevent gas defects - V. I. Chechukha; M. A. Sadokha (Литьë и металлургия)
The formation of defects in the manufacturing of castings is influenced by numerous factors. These factors can affect the quality both individually and in combination. This article provides a characterization of the defects encountered in high‑pressure die casting and identifies the factors influencing their formation. Effective measures are examined to reduce casting defects, which are recommended for obtaining critical and highly demanding castings with stringent surface requirements after mechanical processing.The use of automated high‑pressure die casting complexes in production has a positive impact on the quality of castings, eliminating many of the potential causes of defects related to human factors.